100 years of the Warburg effect: a historical perspective. Issue 12 (7th October 2022) - Hardie, D Grahame
Abstract : Otto Warburg published the first paper describing what became known as the Warburg effect in 1923. All that was known about glucose metabolism at that time was that it occurred in two stages: (i) fermentation (glycolysis) in which glucose was converted to lactate, which did not require oxygen, and (ii) oxidative metabolism, in which the carbon atoms derived from glycolysis were fully oxidized to carbon dioxide, which did require oxygen. Warburg discovered that most tumour tissues produced a large amount of lactate that was reduced but not eliminated in the presence of oxygen, while most normal tissues produced a much smaller amount of lactate that was eliminated by the provision of oxygen. These findings were clearly well ahead of their time because it was another 80 years before they were to have any major impact, and even today the mechanisms underlying the Warburg effect are not completely understood.